Relationship transitional speed agility when rulers freshmen Reconstruction (16 years old) in football - Thari, Ahmed (Journal of Physical Education, 2014)
Have Recent years have shown particular importance of Physical Education, through the evolution of the life of nations and peoples, and this is an indication to the great interest from the presence of specialists and researchers in developing the educational process on an ongoing basis in order to raise the level of sports and achievement in the investment effort. The Fitness is one of the most prominent is the requirement that received study and research to get to the scientific facts that contribute to the development of sports and levels of various fields and levels. The progress in the area of a football game requires ongoing scientific experiments in order to be applied in the field, and that what distinguishes a modern play of speed in performance and move in the field of play, a must-have we preparation and development of referees in line with the level of development in the game. And the game of football one of the most popular sports in the world, to bear the suspense and excitement and great fun for both player practitioner or spectator (the viewer), which depends on several aspects of (player, coach, rulers etc...) and that of the most important aspects are the rules and laws game and applied by the crew of the arbitration author (referee, two judgments assistants, the fourth official), which is the decision-maker and absolute power in the game. Given the importance of the fundamental football in a direct impact on the game of football referees, so we must prepare and qualify referees seriously and scientific methods in the early times and guide trainers about the appropriate capacity in this time period. Hence the importance of research to find out the relationship between the speed and agility of the rulers of the freshmen football, which helps in the development of physical and motor abilities and to develop appropriate training programs in order to raise the level of the referees in the future, which is the first and necessary for the arrival of the rulers to the important tournaments in international forums station.